PENGARUH KEAHLIAN, PENGALAMAN AUDIT DAN SITUASI AUDIT TERHADAP SKEPTISISME PROFESIONAL AUDITOR - Oghy (2017)
This study was conducted to test the Influence of Expertise, Experience Audit and Audit Situation of Auditor Professional Skepticism on BPK. The population in this study is the auditor of BPK RI located in Central Jakarta. The research sample is 48 auditors. Sampling with purposive sampling. The data used are primary data media in the form of a questionnaire. The analysis includes the validity, reliability, classical assumption, hypothesis testing which includes the coefficient of determination (Adjusted R), and the T test and multiple linear regression analysis. The results of this study indicate that significantly influence the expertise and audit situation on the auditor professional skepticism, audit experience does not influence on the auditor professional skepticism. The results of this analysis using the coefficient of determination is known that 38.6 percent of the variation of the auditor's professional skepticism can be explained by the independent variables studied in this research, and by 61.4 percent is explained by other factors outside the model such as the ethic, the competence, the independence, gender, and audit risk.